Perbedaan Persepsi dan Kemandirian Belajar Siswa SMA Pada Mata Pelajaran Matematika antara Kelas IPS dan IPA di Pembelajaran Daring - Rifqi Jannatun Naiim; Yuyu Yuhana; Syamsuri Syamsuri (Universitas Sultan Ageng Tirtayasa, 2021)
This study aims to find differences in the perception and self regulated learning of high school students in mathematics subjects between class X IPA and X IPS in online learning. This study uses a quantitative approach to the type of comparative research. The data collection technique used in this study was a questionnaire on student perceptions and self regulated learning. Data analysis in this study used the Mann Whitney test. The results showed that 1) There was no difference in the perception of high school students in mathematics between class X IPA and class X IPS studies in online learning, but perceptions related to interactions between friends during online learning were more intertwined in social studies class than in science class. 2) There is no difference in the self regulated learning of high school students in mathematics between class X IPA and class X IPS studies in online learning